Ionic Conductivity and Structural Analysis of Carboxymethyl Cellulose Doped With Ammonium Fluoride as Solid Biopolymer Electrolytes - M.A. Ramlli; K.H. Kamarudin; M.I.N. Isa (American-Eurasian Network for Scientific Information publisher, 2024)
Volume :9 Number: 2